2022
DOI: 10.3389/fonc.2022.889575
|View full text |Cite
|
Sign up to set email alerts
|

A New Methodology to Estimate Drug Cost Avoidance in Clinical Trials: Development and Application

Abstract: BackgroundOncology clinical trials can lead to relevant financial savings in drug acquisition for healthcare providers. Considerable methodological heterogeneity is observed among previous studies estimating these savings.MethodsWe developed a methodology to estimate the economic benefit obtained from the enrollment of patients into clinical trials through the analysis of drug cost avoidance. We designed a decision algorithm to determine if a clinical trial is associated with drug cost avoidance. This algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In our study, cancer diseases represent the highest cost-avoidance disease category (79.1%, €6 004 966/€7 591 612). This figure is slightly higher than in previous studies published in 2000 (70%)12 and 2008 (75%) 11. This shift in the share of cancer treatments could be linked to changes in the time horizon and the development of increasingly targeted and expensive therapies and immunotherapies 21 22…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In our study, cancer diseases represent the highest cost-avoidance disease category (79.1%, €6 004 966/€7 591 612). This figure is slightly higher than in previous studies published in 2000 (70%)12 and 2008 (75%) 11. This shift in the share of cancer treatments could be linked to changes in the time horizon and the development of increasingly targeted and expensive therapies and immunotherapies 21 22…”
Section: Discussionmentioning
confidence: 69%
“…Again, the timeline was not the same and our site was not involved in many studies at the time of this work in onco-gynaecology (three clinical trials). For the other most recent studies,12–14 major cost savings were observed for melanoma, breast cancer and genitourinary cancer. The difference between repartition could be explain by the specific expertise of each centre.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One clinical trials unit included in this analysis reported that each €1 in grant funding received, yielded €3 in income from industry for trials, supporting the need for continued expansion and investment in cancer research units nationwide. In international studies, average drug cost avoidance per patient has been estimated at €10,000 to €16,000 [9,10], with cost savings per centre up to €6 million a year [11], significantly exceeding the costs associated with running a clinical trial [12].…”
Section: Introductionmentioning
confidence: 99%